Public Acceptance of Peer-to-Peer Lending as a Digital Payment in Indonesia - Pristiyono Pristiyono; Sipnarong Kanchanawongpaisan; Bayu Eko Broto (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Peer to Peer lending is a financial service model that connects lenders and borrowers to engage in loan agreements directly using Indonesian rupiah through an electronic platform based on internet connectivity. This study investigates the factors that affect behavioral intention and customer satisfaction in the use of Peer-To-Peer (P2P) lending platforms. with a particular emphasis on the novelty of focusing on business actors located around Medan City who utilize P2P lending as an alternative source of capital and business expansion. Employing a quantitative research method. data were collected through online questionnaires distributed via Google Forms. The study targeted Micro, Small, and Medium Enterprises (MSMEs) based in Medan City. involving 504 respondents selected through purposive sampling. Data analysis was conducted using a path analysis model. The findings reveal that performance expectancy. effort expectancy. social influence. intrinsic motivation. and extrinsic motivation all have a positive and significant impact on behavioral intention to adopt P2P lending. Furthermore. behavioral intention was found to have a positive and significant effect on customer satisfaction in the context of P2P lending usage.